Evaluation on the effectiveness of potential endophytic trichoderma spp. From North Sumatra, Indonesia in preventing and suppressing ganoderma boninense infection in oil palm seedlings - Dedek Haryadi (2019)
Basal stem rot (BSR) caused by the fungus Ganoderma boninense is regarded as the most destructive disease of oil palm (Elaeis guineensis Jaqc.) and causes significant economic losses in the oil palm industry of South East Asia. High incidence of BSR affects to the tremendously reduced weight and number of fruit bunches in infected but living palms. Various approaches including chemical, mechanical, cultural and biological measures have been reported to control BSR disease. Unfortunately, no single strategy has yet been able to halt the spreading of the disease. Therefore, a more reliable and integrated strategy that could manage this BSR disease is urgently needed to be further investigated. Application of endophytic biological control agents (BCAs) especially Tiichoderma spp.have been used for decades and shows promising results in supressing Ganoderma infection, beside environmentally safe and sustainable. In this respect, evaluation on the effectiveness of potential endophytic Trichoderma spp. in preventing and suppressing G. boninense infection in oil palm seedlings were investigated in this study. This study aimed to investigate the identity of BSR causal pathogen from North Sumatra, Indonesia and to identify the endophytic Tiichoderma strain from healthy oil palm roots of this area. Thus, to evaluate the antibiosis activity and resistance induced by endophytic Tiichoderma in oil palm seedlings. Identification of Ganoderma isolate from Negeri Lama Estate in North Sumatra, Indonesia was confirmed using Ganoderma selective medium (GSM) and DNA sequence analysis. That latter method showed the isolate from Negeri Lama was closely related to virulent G. boninense isolate GB00l (NCBI accession number: KX092000.l), with a maximum similarity of 99%. Prior to in vitro assessment, all the endophytic BCA isolates from oil palm roots in Negeri Lama Estate studied were first confirmed using Trichoderma selective medium (TSM). Subsequently, DNA sequence analysis identified the BCAs as Tiichoderma species with 99% of similarity for all isolates, where endophytic ETS0l identified as Trichoderma reesei strain RHa (NCBI accession number: KM246746.1), while endophytic ET523 identified as Trichoderma asperellum isolate Fl (NCBI accession number: KP281701.1) and endophytic ET537 identified as Trichoderma asperellum strain Ql (NCBI accession number: HQ293149.1). Antagonistic effects of potential endophytic Trichoderma spp. against G. boninense growth were evaluated via dual culture test and culture filtrate test. The results demonstrated that the percentage inhibition of radial growth (PIRG) of G. boninense were 95.1% in endophytic T. reesei ETS0l, 87.1% in endophytic T. aspere/lum ET523, and 88.9% in endophytic T. asperel/um ET537. In addition, the ability of Trichoderma spp. in suppressing G. boninense growth was also assessed through percentage inhibition of mycelia growth (PIMG). Endophytic T. reesei ETS0l showed the strongest PIMG activity (100%), followed by endophytic T. asperellum ET537 and T. asperellum ET537, 90.5% and 12.3%, respectively. Scanning electron microscopy (SEM) observation was done to reveal the mycoparasitic effect of endophytic Tiichoderma spp. to the G. boninense mycelia. Exposure of endophytic T. reesei ETS0l caused the most severe disruption and lysed effect to the G. boninense mycelium, followed by T. asperellum ET537 and T. asperellum ET523, respectively. Potential bioactive compounds produced by single endophytic Trichoderma spp. and/or during this interaction which inhibiting the G. boninense growth was further investigated using gas chromatography mass spectrometry (GCMS). Several potential antimicrobial compounds such as 3-furaldehyde; pyrazole,1,4-dimethyl-; propanoic acid; 5-methyloxazolidine; pyrrolizin-1,7-dione-6-carboxylic acid, methyl( ester); butanedioic acid; 9-hexadecenoic acid; thiophene, 2,5-dihydro-; 2- bromotetradecanoic acid; 3,4-furandiol, tetrahydro-trans-; 3-methyloxirane-2-carboxylic acid; hydrazine; octadecenoic acid; 2,5-methano-2H-furo[3,2-b]pyran-8-one, hexahydro-; a-bisabolol, etc were also detected. These compounds shall contribute to the antagonistic effect of endophytic Trichoderma spp. against G. boninense. Moreover, to measure the potential of these BCAs in G boninense suppression, an in-viva trial with ten months duration was conducted on oil palm seedlings via G boninense artificial inoculation (rubber wood blocks method) treated with endophytic Trichoderma spp. in the nursery condition. The application of endophytic T. reesei ETSOl found to be the most effective in suppressing BSR with only 13.4% of disease incidence (DI), compared to endophytic T. asperellum ET23 and T. asperellum ET537 with 71.8% and 48.4 % of DI, respectively. The ability of endophytic Trichoderma spp. in inducing resistance of oil palm seedlings was also measured through total phenolic content (TPC) analysis of treated oil palm roots. The results showed all the of endophytic Trichoderma spp. treated seedlings were significantly induced of TPC compared to the control seedlings. Application of endophytic Trichoderma spp. in the nursery exhibited the potential of triggering oil palm seedlings' TPC amount and help in developing resistance in oil palm seedlings, thus protect them from G boninense infection. Therefore, the application of endophytic Trichoderma spp. to the oil palm seedling roots before transplant (at nursery stage) could provide a promising sustainable strategy to manage BSR disease of oil palm. Despite this, there is also a need for further study in evaluating the potential endophytic Trichoderma spp. as a single or consortium approach under field conditions.